O5-S2.05 Role of regional reference laboratories for sexually transmitted infections in improvement of second generation HIV surveillance experience from the Central America Region. (10th July 2011) - Ye, T; Steele, L; Juarez, S I; Chen, C Y; Ballard, R C
Abstract : Background: WHO/UNAIDS recommends National HIV/AIDS and Sexually Transmitted Infection STI) Control Programs to implement integrated HIV, STI and behavioural surveillance to assess the disease burden, and to monitor the temporal trends of HIV/STI prevalence and high-risk sexual behaviours. Despite this recommendation, there is limited STI prevalence data available in many resource poor countries owing to lack of STI laboratory capacity to detect multiple STIs. The CDC STD lab explored the feasibility of a decentralised laboratory strengthening approach by applying more advanced molecular STI diagnostic methods to support the second generation surveillance (SGS) activities in the Central American Region during 2007–2011. Methods: CDC STD lab developed a real-time multiplex PCR (MPCR) to detect Neisseria gonorrhoeae, Chlamydia trachomatis, Trichomonas vaginalis, and Mycoplasma genitalium . In collaboration with regional partners, CDC identified and transferred the diagnostic technology to a regional STI reference laboratory in 2008. The regional reference laboratory provides MPCR testing on specimens collected for surveillance purpose. This standardised SGS study design was implemented at regular intervals in multiple countries in the region to estimate the disease burden and to monitor temporal STI trends. Results: During 2007–2010, four national integrated sexual behavioural and biomarker surveys were implemented using CDC's affiliated regional STI reference center. The quality STI prevalence data was made available to the national HIV/STI programs in Honduras, El Salvador, Nicaragua and Colombia. Similar CDC supported surveillance studies are in-preparation in Guatemala, Belize, Panama, Honduras (second round) and the Dominican Republic. Conclusions: Based on the experience from the Central American Region, it is feasible to implement integrated HIV, STI and behavioural surveillance surveys using robust molecular techniques in resource poor settings. In collaboration with regional partners, CDC's approach to STI laboratory capacity strengthening through establishing a regional reference laboratory should be expanded to other regions.